2010
DOI: 10.1097/phh.0b013e3181e31cee
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of 11 Local Health Department Organizational Networks

Abstract: Context Although the nation’s local health departments (LHDs) share a common mission, variability in administrative structures is a barrier to identifying common, optimal management strategies. There is a gap in understanding what unifying features LHDs share as organizations that could be leveraged systematically for achieving high performance. Objective To explore sources of commonality and variability in a range of LHDs by comparing intraorganizational networks. Intervention We used organizational netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Clancy et al () have led a series of studies that apply the systems science perspective as well as computational models and simulation for purposes such as predicting the impact of the EHR on practice patterns. In terms of survey data, Merrill, Keeling, and Carley () collected data from 11 public health departments and used organizational network analysis, a computational method derived from social network analysis, to examine the linkage between network structure and performance on essential public health services. Using social media as a big data source, Yoon and colleagues applied data mining and other computational techniques to a large corpus of Tweets related to physical activity to assess content, sentiments, and network structures (Yoon & Bakken, ; Yoon, Elhadad, & Bakken, ).…”
Section: Nursing Needs Big Data and Data Sciencementioning
confidence: 99%
“…Clancy et al () have led a series of studies that apply the systems science perspective as well as computational models and simulation for purposes such as predicting the impact of the EHR on practice patterns. In terms of survey data, Merrill, Keeling, and Carley () collected data from 11 public health departments and used organizational network analysis, a computational method derived from social network analysis, to examine the linkage between network structure and performance on essential public health services. Using social media as a big data source, Yoon and colleagues applied data mining and other computational techniques to a large corpus of Tweets related to physical activity to assess content, sentiments, and network structures (Yoon & Bakken, ; Yoon, Elhadad, & Bakken, ).…”
Section: Nursing Needs Big Data and Data Sciencementioning
confidence: 99%
“…Understanding social network characteristics among stakeholders and potential partners often facilitated determinations of county capacity (Merrill, Keeling, & Carley, 2010; Schensul, 2009). Perceived competition and local control are significant concerns, whether in rural communities or elsewhere (Chavis, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of a large body of empirical research on knowledge transmission in social networks concludes that " [m]any studies across all levels have found that a central network position, defined either in terms of the number of direct contacts or both direct and indirect contacts, has a positive influence on knowledge creation, transfer, and adoption" (Phelps et al, 2012(Phelps et al, , 1138. An emerging literature on networks of health policy practitioners in domestic contexts also tends to stress the benefits that network connections can bring to performance (Blanchet & James, 2013;Blanchet et al, 2014;Browne et al, 2017;Gold et al, 2008;Jippes et al, 2010;Khosla et al, 2016;Merrill et al, 2010;Pagliccia et al, 2010;Weishaar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%